Evaluation of the CIPPO Model in the Processing Training Program at the Central Java Vocational Training and Transmigration Center - Savinka, Kayla Nawalani; Malik, Abdul (Universitas Negeri Semarang, 2025)
The sustainable development goals set by the United Nations emphasize the importance of balancing economic growth, social welfare, and environmental conservation to achieve a better and more sustainable life. Indonesia has a high number of productive-age citizens, but this figure is not balanced with the available jobs. Currently, Indonesia still has a high unemployment rate, and this training program is expected to reduce unemployment and poverty in Indonesia. This study aims to evaluate the vocational training program in food processing at the Vocational Training and Transmigration Center of Central Java Province in achieving the program's success objectives. Adopting a qualitative approach with a case study, data was collected through in-depth interviews with the Head of the Vocational Training Center, training instructors, and three selected alumni participants based on post-training monitoring results. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, focusing on the components (Context, Input, Process, Product, Outcome). The research results indicate that the training program has proven effective in reducing unemployment and empowering communities through needs-based and locally-oriented training. As a result of the training, participants successfully developed independent businesses with significant increases in income.